Occupational Allergic Sensitization Among Workers Processing King Crab (Paralithodes camtschaticus) and Edible Crab (Cancer pagurus) in Norway and Identification of Novel Putative Allergenic Proteins - Thomassen, Marte R.; Kamath, Sandip D.; Bang, Berit E.; Nugraha, Roni; Nie, Shuai; Williamson, Nicholas A.; Lopata, Andreas L.; Aasmoe, Lisbeth (Frontiers in Allergy, 2021)
Introduction: Asthma and allergy occur frequently among seafood processing workers, with the highest prevalence seen in the crustacean processing industry. In this study we established for the first time the prevalence of allergic sensitization in the Norwegian king- and edible crab processing industry and characterized the IgE-reactive proteins. Materials and Methods: Two populations of crab processing workers participated; 119 king crab and 65 edible crab workers. The investigation included information on work tasks and health through a detailed questionnaire. Allergic sensitization was investigated by crab-specific IgE quantification and skin prick tests (SPT) to four in-house prepared crab extracts; raw meat, cooked meat, raw intestines and raw shell. Allergen-specific IgE binding patterns were analyzed by IgE immunoblotting to the four allergen extracts using worker serum samples. Total proteins in crab SPT extracts and immunoblot-based IgE binding proteins were identified by mass spectrometric analysis. Results: Positive SPTs were established in 17.5% of king- and 18.1% of edible crab workers, while elevated IgE to crab were demonstrated in 8.9% of king- and 12.2% of edible crab processing workers. There was no significant difference between the king and edible crab workers with respect to self-reported respiratory symptoms, elevated specific IgE to crab or SPT results. Individual workers exhibited differential IgE binding patterns to different crab extracts, with most frequent binding to tropomyosin and arginine kinase and two novel IgE binding proteins, hemocyanin and enolase, identified as king- and edible crab allergens. Conclusions: Occupational exposure to king- and edible crabs may frequently cause IgE mediated allergic sensitization. Future investigations addressing the diagnostic value of crab allergens including tropomyosin and arginine kinase and the less well-known IgE-binding proteins hemocyanin and enolase in a component-resolved diagnostic approach to crab allergy should be encouraged.